Daya Saing, pengangguran, dan kemiskinan di Sulawesi Tengah - Suparman, Suparman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The research objective is to measure the impact of regional competitiveness, unemployment and poverty in Central Sulawesi Province using the 2017-2019 database. Panel regression model is used to estimate the effect of competitiveness on unemployment and poverty. The results of this research find that regional competitiveness has a negative and significant influence on the depth of poverty in Central Sulawesi Province.